Pengembangan Alat Uji Keandalan IC Op-Amp Tipe Single, Dual dan Quad Berbasis ESP32 - Arwin Pamungkas; Rayuh Dhilah Hanggara; Enas Dhuhri Kusuma (Jurnal Pengelolaan Laboratorium Pendidikan, 2026)
Accurate reliability testing of Operational Amplifiers Integrated Circuit (IC Op-Amps) is essential in education and device repair. This study aims to develop a portable reliability test tool for single, dual, and quad Op-Amp ICs based on the ESP 32 microcontroller with high testing accuracy. The research method used is research and development. The device is equipped with a 3.7 V lithium battery with 2000 mAh capacity, which can be recharged via Type-C USB connector. It features a rotary encoder for command and menu navigation, an Organic Light Emitting Diode (OLED) for menu and test result display. The IC testing process includes generating reference signal, reading output signal, comparing it with the input signal, and determining the status as “OK” or “Faulty.” Testing was conducted on several IC types, including LM741, LM358, and LM324. Results indicate that the device can identify IC defects with 100% accuracy. Battery endurance testing showed a lifespan up to ±10 hours active use, plus ±10 hours standby time, and perform over 1,900 testing cycles without performance degradation. With its compact design, standalone operation, and testing accuracy, this device has great potential to become a reliable solution for troubleshooting and learning process, particularly in electrical engineering laboratories.